PROPERTIES OF BIOACTIVE SUBSTANCES AGAINST TOXIC HEPATITIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Liver damage is caused by endogenous or exogenous factors. When the body is exposed to harmful stimuli, an excessive amount of reactive oxygen species is formed and leads to an imbalance between oxidation and antioxidant systems, resulting in oxidative stress. One of the main etiologies of liver damage is oxidative stress. Some plants contain antioxidants such as polyphenols, polysaccharides, carotenoids, lentinan, vitamin C, and vitamin E. These phytochemicals have antioxidant activity, which in vivo purify free radicals and maintain liver health.